Detection and partial characterization of proenkephalin mRNA. - Gubler, U (1981)
We have used an oligodeoxynucleotide of defined sequence to detect and quantitate proenkephalin mRNA in the poly(A)-containing fraction of RNA from bovine adrenal medullas. The decahexamer 5'-d(G-G-T-A-G-T-C-C-A-T-C-C-A-C-C-A)-3' was synthesized to be complementary to the codons specifying the amino acid sequence NH2-Trp-Trp-Met-Asp-Tyr-Gln-COOH. This stretch of amino acids occurs in peptide I, one of the intermediates in the biosynthetic pathway of the enkephalins in bovine adrenal medulla. This pathway starts with a precursor (proenkephalin) of about 45 kilodaltons [Stern, A. S., Jones, B. N., Shively, J. E., Stein, S. & Udenfriend, S. (1981) Proc. Natl. Acad. Sci. USA 78, 1962-1966]. The decahexamer hybridized to adrenal poly(A)+RNA and was extended into cDNA with reverse transcriptase (RNA-dependent DNA nucleotidyltransferase). Five main discrete products ranging in size from 115 to 168 nucleotides were observed. The sequences of these extensions were found to be identical over the approximately 70 nucleotides sequenced from their 5' termini and corresponded exactly to the sequence expected from the amino acid sequence of peptide I. These cDNAs and the decahexamer itself hybridized to an adrenal medullary poly(A)+RNA species of about 1500 nucleotides, sufficient in size to code for the proposed proenkephalin. At saturation, approximately 2 fmol of the decahexamer were bound per microgram of mRNA; thus, the proenkephalin mRNA represents about 0.1% of the total poly(A)+RNA population in the tissue.